Un trial di efficacia nella prevenzione degli infortuni nel settore del legno / Effectiveness trial for prevention of occupational injuries in the wood processing industry - Olivieri, A.; Bizzotto, S.; Zecchin, et al., F. (La Medicina del Lavoro, 2009)
La formazione è considerata uno strumento cardine per promuovere la cultura della sicurezza e della prevenzione nei luoghi di lavoro. Tuttavia, pochi sono gli studi che valutano la qualità dell’offerta formativa e i suoi risultati. È stato quindi avviato un trial di comunità randomizzato e controllato, volto a verificare l’efficacia pratica di un intervento di formazione rivolto ai datori di lavoro, per la riduzione del rischio infortunistico. Scopo del presente lavoro è quello di descrivere il disegno di studio e l’intervento di formazione (trattamento), sottolineando gli aspetti più significativi. Effectiveness trial for prevention of occupational injuries in the wood processing industry Background: Training is a key tool to improve prevention and safety management at the workplace. Few studies have aimed at assessing quality of training and its outcomes. Objectives and methods: This paper describes the rationale, design, content, and evaluation of an ongoing randomized controlled trial aimed at assessing the effectiveness of a training programme designed to reduce the risk of occupational injuries among employees of the wood processing industry. Discussion and conclusions: Well designed, targeted training programmes could represent a feasible means of reducing work injuries by improving employers’ behaviour and attitudes towards safety; nevertheless, these kinds of interventions have a considerable impact both in terms of human resources and in terms of cost. For these reasons, assessment of effectiveness and knowledge-sharing should be considered as essential phases of injury prevention programmes.